A study of self-efficacy, social support, and well-being in working and non-working women of Darbhanga City. (International Journal of Food and Nutritional Sciences, 2022)
This study aimed to evaluate the self-efficacy, social support, and overall well-being of women in Darbhanga City, both those who work and those who do not. The study also explored the inter-relationship among these variables and whether they differed between working and non-working women. To achieve this, 400 women were included in the study, with 200 working and 200 non-working women selected through purposive-cum-incidental sampling. Several scales were employed to measure the well-being, self-efficacy, and social support of the participants.